Community, liberalism, and Christian ethics - Fergusson, David (Cambridge University Press, 1998)
This book is an examination of current issues in the related fields of moral philosophy and Christian theology. It raises the question of whether and to what extent Christian moral presuppositions are distinctive or are held in common with other persons and communities. Attention is devoted to debates in pluralist societies about the relation of moral belief and action to tradition, community and story. A mediating position is advocated whereby recognition is accorded to both the distinctiveness of Christian convictions and their overlap with other moral positions